IMPLEMENTASI KEBIJAKAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) DI KECAMATAN TUAH MADANI TAHUN 2021 (STUDI KASUS PADA KELURAHAN SIALANGMUNGGU) - Nurul Izza; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the implementation of the policy for imposing restrictions on community activities (PPKM) in the Sialangmunggu Village, as well as knowing the supporting factors for the implementation of the policy for imposing restrictions on community activities (PPKM) in the Sialangmunggu Village. This research is a descriptive research with a qualitative approach. Data was collected through interviews and documentation. PPKM activitives in Sialangmunggu Village include: setting operating housrs, limiting restaurant/stalls/cafes and other businesses, limitimg the capacity of places of worship and enforcing strict health protocols in public facilities and social activitives by implementing 5M. In the study, researchers used Edward III’s theory in Widodo (2010:96) there are 4 factors, namely: (1) communication, (2) resources, (3) disposition and (4) bureaucratic structure. This research can be concluded that the communication carried out by the kelurahan with RT/RW and the community has been going well, the resources used by the kelurahan in field implementation involve staff, namely village officials, Bhabinsa, Bhabinkatibmas, RT/RW and the community, the diposition in implementing PPKM activities is quite good and also the implementers of the policy deserve appreciation, the bureaucratic structure is determined by the village administration, namely Bhabinsa, Bhabinkatibmas, RT/RW, village officials and the community. Supporting factors in the implementation of the policy for restricting community activities(PPKM), namely 1. Availability of founds for PPKM and 2. Avaibility of resources. Keywords: policy implementation, communication, resources, disposition, Covid-19 bureaucraticstructure